Preparation method and application of bimetal MOF (Metal Organic Framework) modified nanofiber membrane with antibacterial property

PDA-PAN nanofiber membrane was prepared through electrospinning technology and modified into bimetallic MOF, which solved the problem of insufficient processability and antibacterial performance of MOF composite electrospinned fiber membrane, and achieved efficient antibacterial effect, which was suitable for applications in the field of water treatment. .

CN119145226AInactive Publication Date: 2024-12-17TIANJIN POLYTECHNIC UNIV

Patent Information

Application Number
CN202310706649.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing MOF composite electrospun fiber membrane preparation methods have problems such as poor processability, high brittleness and insufficient antibacterial performance, which is difficult to effectively reduce membrane pollution and improve water treatment efficiency.

Method used

Electrospinning technology was used to prepare PDA-PAN nanofiber membranes, and modified by immersion in a mixed solution of cobalt acetate and zinc nitrate, and then reacted in 2-methylimidazole solution to form a bimetallic MOF@PDA-PAN nanofiber membrane. , improve its antibacterial properties.

Benefits of technology

It has achieved efficient antibacterials against E.coli and S.aureus, with an antibacterial rate of 99.9%, and is simple to operate and mild in conditions, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145226A_ABST
    Figure CN119145226A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a bimetallic MOF modified nanofiber membrane with antibacterial performance, which comprises the following steps: 1) adding polyacrylonitrile and a pore-foaming agent into an organic solvent, uniformly stirring and mixing at room temperature, carrying out electrostatic spinning to obtain primary fibers, soaking the primary fibers to remove the pore-foaming agent, and drying to obtain a polyacrylonitrile nanofiber membrane; (2) putting the polyacrylonitrile nanofiber membrane into a Tris-HCl buffer solution of dopamine hydrochloride to carry out self-polymerization reaction, and then washing and drying a product to obtain a dopamine modified polyacrylonitrile nanofiber membrane; and 3) immersing the modified membrane in a mixed solution of cobalt acetate and zinc nitrate, reacting at room temperature, then immersing the fiber membrane in an organic ligand solution for full reaction, washing with deionized water, and drying to obtain a target product. The antibacterial rate of the bimetal MOF modified nanofiber membrane prepared by the method can reach 60% or above within 1 h, the antibacterial rate of the bimetal MOF modified nanofiber membrane prepared by the method reaches 99.9% within 24 h, and the purpose of fast and efficient antibacterial is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nanofiber composite membrane preparation, and specifically relates to a preparation method and application of a bimetallic MOF modified nanofiber membrane with antibacterial properties. Background Art

[0002] Membrane technology based on polymer membranes has been widely recognized in the fields of seawater desalination and wastewater treatment, and has rapidly become popular due to its advantages such as energy saving and environmental protection, good reusability, high efficiency and wide application range. However, the problem of microbial contamination caused by biofilm formation has become one of the main challenges of membrane technology. Therefore, the development of a membrane material with excellent antibacterial and anti-fouling properties can effectively reduce the occurrence of membrane fouling.

[0003] Metal-Organic Framework (MOF) is a porous material composed of metal ions and organic ligands. It is widely used in antibacterial, drug delivery, adsorption, catalysis and water treatment due to its various crystal structures, rich porosity, adjustable functions, inherent biodegradability and good biocompatibility. MOF materials are mostly in the form of powders, which have disadvantages such as poor processability and brittleness, and their practical application in water treatment is limited. Electrospun nanofiber membranes are ideal substrates for MOF crystal deposition due to their specific structural parameters and chemical stability.

[0004] At present, there are four main methods for preparing MOF composite electrospun fiber membranes, namely, blending method, in-situ growth method, layer-by-layer self-assembly method and secondary growth method. CN 115138393 A discloses an in-situ synthesized irregular MOF photocatalyst and a preparation method thereof, wherein polyacrylonitrile (PAN) fiber is modified with amidoxime to prepare an irregular MOF photocatalyst. This method can significantly improve the visible spectrum response range and photocatalytic activity of the MOF photocatalyst, but the amidoxime modification has a significant destructive effect on the structure of the fiber membrane itself, which will affect the mechanical properties of the membrane. There is research (J.Mater.Chem.A, 2018, 6, 15807 - 15814) reported a method for preparing zeolitic imidazolate framework material @ polyacrylonitrile (ZIF@PAN) fibers that can simultaneously adsorb formaldehyde and efficiently filter PM2.5. Cobalt acetate (Co(AC)2) was introduced into PA during the electrospinning process. NThen PAN / Co(AC)2 was immersed in 2-methylimidazole to prepare MOF core-shell fiber material, but the conversion rate of PAN / Co(AC)2 to ZIF@PAN was very slow, the reaction time was long, and due to the loss of some precursors, the loading amount of MOF on the surface of nanofibers was reduced. The secondary growth rule separates the MOF seed nucleation and growth steps. Compared with the layer-by-layer self-assembly method and the in-situ growth method, it is less likely to have defective MOFs, and it is easier to control the microstructure of the membrane, while avoiding the phenomenon of uneven MOF particles in the blending method. Therefore, it is of great practical significance to develop a MOF composite fiber membrane that is simple to operate, mild in conditions, easy to mass produce, and has good stability and excellent antibacterial properties. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a method for preparing a bimetallic MOF-modified nanofiber membrane with antibacterial properties. The antibacterial rates of the prepared nanofiber membrane against E. coli and S. aureus are 60% and 65% respectively after being cultured for 1 hour, and the antibacterial rates reach 99.9% after being cultured for 24 hours, thereby achieving the purpose of efficient and rapid antibacterial.

[0006] To this end, the technical solution of the present invention is as follows:

[0007] The preparation method and application of bimetallic MOF modified nanofiber membrane with antibacterial properties include the following steps:

[0008] 1) Preparation of PDA-PAN nanofiber membrane: PAN and porogen are added to an organic solvent, stirred and mixed at room temperature, and electrospun to obtain primary fibers. The primary fibers are soaked to remove the porogen, and then dried to obtain a PAN nanofiber membrane. A certain amount of dopamine hydrochloride is dissolved in a Tris-HCl buffer solution, and the PAN nanofiber membrane is soaked in the above solution for self-polymerization. Then, the polydopamine (PDA) modified PAN nanofiber membrane is ultrasonically treated to remove excess PDA particles adhering to the nanofibers, and the PDA-PAN nanofiber membrane is obtained after air drying.

[0009] The porogen increases the surface area of ​​the fiber membrane, thereby increasing the active sites for MOF growth.

[0010] 2) Preparation of bimetallic MOF modified nanofiber membrane: The PDA-PAN nanofiber membrane was placed in a mixed solution of cobalt acetate and zinc nitrate with a concentration of 0.5-5 mol / L, and reacted at room temperature for 0.5-2 h. The fiber membrane was then immersed in a certain concentration of organic ligand (2-methylimidazole, 2-M1M) solution and reacted for 6-24 h. The membrane was then rinsed with deionized water and dried at 50°C to obtain a bimetallic MOF modified nanofiber membrane (Co / Zn-MOF@PDA-PAN nanofiber membrane).

[0011] The organic ligand 2-MIM has good solubility and stability, can form coordination bonds with metal ions, help the formation and crystal growth of ZIF, improve the preparation efficiency and quality of ZIF, and can control the lattice structure and pore size of ZIF, so that ZIF has better application performance.

[0012] Furthermore, the porogen in step 1) is ethanol, isopropanol, acetone, polyvinyl pyrrolidone, polyethylene glycol, zinc chloride or calcium carbonate.

[0013] Furthermore, the organic solvent in step 1) is one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, or a mixed solvent thereof.

[0014] Furthermore, the conditions for electrospinning in step 1) are: voltage of 18-23 kV, receiving distance of 10-30 cm, spinning solution flow rate of 0.5-2 mL / h, spinning temperature of 20-30° C., humidity of 20-40%; and the needle used is a 19-23 gauge needle.

[0015] Furthermore, the concentration of the dopamine hydrochloride solution in step 1) is 1 to 10 mg / mL.

[0016] Furthermore, in step 2), the concentration of the organic ligand is 0.08 mol / L to 0.96 mol / L.

[0017] Furthermore, the organic ligand in step 2) is 2-ethylimidazole, 2-propylimidazole, 2-isopropylimidazole, 2-methylbenzimidazole, 2-methyl-4-ethylimidazole, 2-methyl-4-isopropylimidazole, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, etc.

[0018] Furthermore, in step 2), the molar ratio of the bimetallic salt to the organic ligand is 3:1 to 1:3.

[0019] Furthermore, in step 2), the molar ratio of the bimetallic salts is 5:1 to 1:5.

[0020] Furthermore, the bimetallic salt in step 2) is copper nitrate, zirconium nitrate, nickel nitrate, ferric chloride, etc.

[0021] Compared with the prior art, the technical solution provided by the present invention has the following advantages:

[0022] 1) Electrospinning technology was used to produce nanofibers with high porosity, high specific surface area and excellent surface hydrophilicity, achieving anti-adhesion properties against bacteria (Gram-negative and Gram-positive bacteria); 2) Dopamine deposition modification on the surface of nanofibers can effectively increase the growth points of MOF, and obtain a nanofiber membrane with a densely grown MOF layer on the surface, which has excellent antibacterial properties (the antibacterial rates against Escherichia coli and Staphylococcus aureus both reached 99.9%); 3) The antibacterial rate of the bimetallic MOF-modified nanofiber membrane in 1 hour reached more than 60%, achieving the purpose of rapid and efficient antibacterial. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 a is the SEM image (×10000) of the PAN nanofiber membrane obtained in Example 1;

[0024] Figure 1 b is the SEM image of PDA-PAN2 nanofibers obtained in Example 2 (×10000);

[0025] Figure 1 c is the SEM image of Co / Zn-MOF@PDA-PAN0.16 nanofibers obtained in Example 3 (×10000);

[0026] Figure 1 d is the SEM image of Co / Zn-MOF@PDA-PAN0.24 nanofibers obtained in Example 4 (×10000);

[0027] Figure 2 XPS graphs of PAN obtained in Example 1, PDA-PAN2 obtained in Example 2, and Co / Zn-MOF@PDA-PAN0.16 nanofibers obtained in Example 3;

[0028] Figure 3 a is the antibacterial effect of the PDA-PAN2 nanofiber membrane prepared in Example 2 and cultured with E. coli for different time periods;

[0029] Figure 3 b shows the antibacterial effect of the PDA-PAN2 nanofiber membrane prepared in Example 2 and cultured with S. aureus for different time periods;

[0030] Figure 3 c is the antibacterial effect of the Co / Zn-MOF@PDA-PAN0.16 nanofiber membrane prepared in Example 3 and cultured with E.coli for different time periods;

[0031] Figure 3d is the antibacterial effect of the Co / Zn-MOF@PDA-PAN0.16 nanofiber membrane prepared in Example 3 and cultured with S. aureus for different time periods;

[0032] Figure 4 These are SEM images of the PNA prepared in Example 1, the PDA-PAN2 obtained in Example 2, and the Co / Zn-MOF@PDA-PAN0.16 nanofiber membrane obtained in Example 3 after being cultured with E. coli and S. aureus for 24 hours. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0034] The antibacterial performance experiments were conducted on the PNA, PDA-PAN2 and Co / Zn-MOF@PDA-PAN0.16 nanofiber membranes prepared in some examples. The specific process is as follows:

[0035] ① Preparation of Luria-Bertani (LB) liquid culture medium and solid culture medium: 10g peptone, 5g yeast extract powder and 10g NaCl are fully dissolved in 1L distilled water, and the pH of the LB liquid culture medium is adjusted to 7.2-7.4 with NaOH solution. After sterilization in a 120℃ high-pressure steam sterilizer, it is placed in a clean bench for use. The preparation method of LB solid culture medium is to add 10g peptone, 5g yeast extract powder, 10g NaCl and 20g agar to 1L distilled water, heat in an 80℃ water bath to fully dissolve, and then sterilize in a 120℃ high-pressure steam sterilizer, pour into a sterile culture dish in a clean bench and dry naturally for use. E. coli and S. aureus were inoculated into 200mL LB liquid culture medium, and the bacterial solution concentration was fixed at 10 7 ~10 8 CFU / mL is reserved.

[0036] ② Plate count method

[0037] The antibacterial properties of Co / Zn-MOF@PDA-PAN nanofiber membranes were tested by the plate count method. First, 40 mg of the sample was weighed, sterilized by ultraviolet irradiation, and added to a phosphate buffer solution (PBS, pH = 7.4). 7 ~10 8 CFU / mL), and cultured in a constant temperature incubator at 37°C. Finally, the bacterial suspensions at 1, 24 hours after culture with the sample were selected, diluted step by step with sterile water, and 0.1 mL of each bacterial suspension with three different concentration gradients was selected to spread on a plate, and cultured in a constant temperature incubator at 37°C for 24 hours, and the antibacterial rate of each sample was calculated.

[0038] ③SEM observation of bacterial morphology

[0039] The bacterial morphology on the surface of PAN, PDA-PAN and Co / Zn-MOF@PDA-PAN nanofiber membranes was observed by SEM. The samples sterilized by UV irradiation were cultured with the bacterial suspension in a constant temperature incubator at 37°C for 24 hours. After taking out the samples, the sample surface was rinsed with PBS to avoid residual bacteria on the surface. After rinsing, the samples were fixed in a 2.5% glutaraldehyde solution at 4°C for 5 hours. The fixed samples were immersed in 25%, 50%, 75% and 100% ethanol solutions for dehydration and washing, each time for 15 minutes. Finally, the samples were dried, sprayed with gold, and observed by SEM.

[0040] Example 1

[0041] The preparation method and application of bimetallic MOF modified nanofiber membrane with antibacterial properties include the following steps:

[0042] 1) Preparation of PDA-PAN nanofiber membrane: Weigh 1.76g PAN and add it to 10g DMF, stir for 10h to obtain a 15wt% solution. Then add 0.1g PVP and stir magnetically for 25min to obtain PAN spinning solution. The spinning solution was loaded into a syringe and an electrospinning machine was used to form a PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1mL / h, receiving distance 15cm, spinning time 4h, humidity <30%. The PAN fiber membrane was immersed in a 1mg / mL dopamine hydrochloride solution for about 16h for self-polymerization. Then, the fiber membrane was ultrasonically treated for 10min to remove excess PDA particles adhering to the nanofibers, rinsed three times with deionized water, and dried at 80℃ for 6h to obtain a PDA-PAN1 nanofiber membrane.

[0043] 2) Preparation of Co / Zn-MOF@PDA-PAN nanofiber membrane: The PDA-PAN1 nanofiber membrane was placed in a mixed solution of Co(AC)2·4H2O and Zn(NO3)2·6H2O with a concentration of 1.0 mol / L, and reacted at room temperature for 2 h. The fiber membrane was then immersed in a 0.08 mol / L 2-MIM solution and reacted for 18 h. The fiber membrane was then rinsed with deionized water and dried at 50°C to obtain a Co / Zn-MOF@PDA-PAN0.08 nanofiber membrane.

[0044] Depend on Figure 1 a It can be seen that the fiber diameter is uniform and the surface is smooth without any protrusions and grooves.

[0045] Depend on Figure 2 It can be seen that the binding energy of PAN fiber membrane corresponds to the XPS peaks of C1s, N1s and O1s at 284.9 eV, 399.1 eV and 532.1 eV, respectively.

[0046] Depend on Figure 4 As shown, the PAN nanofiber membrane has no antibacterial adhesion and antibacterial effects, so a large number of bacteria with complete morphology and smooth surface adhere to the membrane surface, E. coli is rod-shaped, and S. aureus is spherical.

[0047] Example 2

[0048] The preparation method and application of bimetallic MOF modified nanofiber membrane with antibacterial properties include the following steps:

[0049] 1) Preparation of PDA-PAN nanofiber membrane: Weigh 1.76g PAN and add it to 10g DMF, stir for 10h to obtain a 15wt% solution. Then add 0.1g PVP and stir magnetically for 25min to obtain PAN spinning solution. The spinning solution was loaded into a syringe and an electrospinning machine was used to form a PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1mL / h, receiving distance 15cm, spinning time 4h, humidity <30%. The PAN fiber membrane was soaked in a 2mg / mL dopamine hydrochloride solution for about 12h for self-polymerization. Then, the fiber membrane was ultrasonically treated for 10min to remove excess PDA particles adhering to the nanofibers, rinsed three times with deionized water, and dried at 80℃ for 6h to obtain a PDA-PAN2 nanofiber membrane.

[0050] 2) Preparation of Co / Zn-MOF@PDA-PAN nanofiber membrane: The PDA-PAN2 nanofiber membrane was placed in a mixed solution of Co(AC)2·4H2O and Zn(NO3)2·6H2O with a concentration of 1.0 mol / L, and reacted at room temperature for 2 h. The fiber membrane was then immersed in a 0.08 mol / L 2-MIM solution and reacted for 12 h. The fiber membrane was then rinsed with deionized water and dried at 50°C to obtain a Co / Zn-MOF@PDA-PAN0.08 nanofiber membrane.

[0051] Depend on Figure 1 b It can be seen that PDA is evenly wrapped on the surface of a single fiber, the fiber diameter is uniform, and the surface is smooth; compared with the PAN nanofiber membrane, the average diameter of the PDA-PAN2 fiber increases with the increase of DA mass concentration

[0052] Depend on Figure 2 It can be seen that the O1s content increases after PDA modification. Compared with the PAN nanofiber membrane, the O / C atom content ratio in PDA-PAN2 increases significantly, which is also the result of PDA modification of PAN nanofiber membrane.

[0053] Depend on Figure 3As shown in a and b, the antibacterial properties of the nanofiber membrane were further analyzed by the plate counting method. The PDA-PAN2 nanofiber membrane showed weak antibacterial properties, and PDA itself had no antibacterial properties. This may be because a small amount of bacteria adhered to the surface of the PDA-PAN2 nanofiber membrane, resulting in a decrease in the amount of bacteria in the bacterial suspension, thus showing antibacterial properties.

[0054] Depend on Figure 4 As shown in the figure, compared with PAN nanofiber membrane, the number of bacteria adhering to the surface of PDA-PAN2 nanofiber membrane decreased after PDA modification. Since PDA molecules contain a large number of hydrophilic groups such as hydroxyl and amino groups, the hydrophilicity of PDA-PAN2 is improved. When the fiber membrane modified by PDA is cultured with bacterial solution, a water layer is first formed on the fiber surface, thereby preventing some bacteria from adhering to the fiber surface. However, a small amount of bacteria still adhere to the membrane surface, which is consistent with the Figure 3 The plate count test results were consistent.

[0055] Example 3

[0056] The preparation method and application of bimetallic MOF modified nanofiber membrane with antibacterial properties include the following steps:

[0057] 1) Preparation of PDA-PAN nanofiber membrane: Weigh 1.76g PAN and add it to 10g DMF, stir for 10h to obtain a 15wt% solution. Then add 0.1g PVP and stir magnetically for 25min to obtain PAN spinning solution. The spinning solution is loaded into a syringe and an electrospinning machine is used to form a PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1mL / h, receiving distance 15cm, spinning time 4h, humidity <30%. The PAN fiber membrane was soaked in a 2mg / mL dopamine hydrochloride solution for about 12h for self-polymerization. Then, the fiber membrane was ultrasonically treated for 10min to remove excess PDA particles adhering to the nanofibers, rinsed three times with deionized water, and dried at 80℃ for 6h to obtain a PDA-PAN2 nanofiber membrane.

[0058] 2) Preparation of Co / Zn-MOF@PDA-PAN nanofiber membrane: The PDA-PAN2 nanofiber membrane was placed in a mixed solution of Co(AC)2·4H2O and Zn(NO3)2·6H2O with a concentration of 1.0 mol / L, and reacted at room temperature for 2 h. The fiber membrane was then immersed in a 0.16 mol / L 2-MIM solution and reacted for 12 h. The membrane was then rinsed with deionized water and dried at 50°C to obtain a Co / Zn-MOF@PDA-PAN0.16 nanofiber membrane.

[0059] like Figure 1As shown in c, the number of Co / Zn-MOF nanoparticles on the surface of Co / Zn-MOF@PDA-PAN0.16 fiber membrane increases.

[0060] Depend on Figure 2 It can be seen that in addition to the XPS peaks of C1s, N1s and O1s on the Co / Zn-MOF@PDA-PAN0.16 spectrum, peaks of Co and Zn elements can also be observed, indicating that Co / Zn-MOF nanoparticles are successfully grown on the surface of PDA-PAN fibers.

[0061] Depend on Figure 3 As shown in c and d, the Co / Zn-MOF@PDA-PAN0.16 nanofiber membrane showed obvious antibacterial effect after being cultured with the bacterial solution for 1 hour, and the antibacterial rates of the nanofiber membrane against E. coli and S. aureus were 59.6% and 64.9%, respectively; after co-culture for 3 hours, the antibacterial rates of the Co / Zn-MOF@PDA-PAN0.16 nanofiber membrane against E. coli and S. aureus reached 76% and 99.4%, respectively, and were above 99% after 24 hours, indicating that the Co / Zn-MOF@PDA-PAN nanofiber membrane has rapid antibacterial properties.

[0062] Depend on Figure 4 It can be seen that after the Co / Zn-MOF@PDA-PAN0.16 fiber membrane was cultured with bacteria for 24 hours, almost no bacteria adhered to the membrane surface, indicating that the Co / Zn-MOF@PDA-PAN nanofiber membrane has obvious antibacterial and anti-adhesion properties.

[0063] Example 4

[0064] The preparation method and application of bimetallic MOF modified nanofiber membrane with antibacterial properties include the following steps:

[0065] 1) Preparation of PDA-PAN nanofiber membrane: Weigh 1.76g PAN and add it to 10g DMF, stir for 10h to obtain a 15wt% solution. Then add 0.1g PVP and stir magnetically for 25min to obtain PAN spinning solution. The spinning solution was loaded into a syringe and an electrospinning machine was used to form a PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1mL / h, receiving distance 15cm, spinning time 4h, humidity <30%. The PAN fiber membrane was soaked in a 2mg / mL dopamine hydrochloride solution for about 12h for self-polymerization. Then, the fiber membrane was ultrasonically treated for 10min to remove excess PDA particles adhering to the nanofibers, rinsed three times with deionized water, and dried at 80℃ for 6h to obtain a PDA-PAN2 nanofiber membrane.

[0066] 2) Preparation of Co / Zn-MOF@PDA-PAN nanofiber membrane: The PDA-PAN2 nanofiber membrane was placed in a concentration of 1 . The fiber membrane was immersed in a mixed solution of 0.0 mol / L Co(AC)2·4H2O and Zn(NO3)2·6H2O and reacted at room temperature for 2 h. Then, the fiber membrane was immersed in a 0.24 mol / L 2-MIM solution and reacted for 12 h. Then, it was rinsed with deionized water and dried at 50 °C to obtain a Co / Zn-MOF@PDA-PAN0.24 nanofiber membrane.

[0067] Comparative Examples 1, 2, and 3, as Figure 1 d It can be seen that with the increase of ligand concentration, the number of Co / Zn-MOF nanoparticles on the surface of Co / Zn-MOF@PDA-PAN0.24 fiber membrane increased significantly.

[0068] Example 5

[0069] The preparation method and application of bimetallic MOF modified nanofiber membrane with antibacterial properties include the following steps:

[0070] 1) Preparation of PDA-PAN nanofiber membrane: Weigh 1.76g PAN and add it to 10g DMF, stir for 10h to obtain a 15wt% solution. Then add 0.1g PVP and stir magnetically for 25min to obtain PAN spinning solution. The spinning solution was loaded into a syringe and an electrospinning machine was used to form a PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1.5mL / h, receiving distance 20cm, spinning time 4h, humidity <30%. The PAN fiber membrane was immersed in a 3mg / mL dopamine hydrochloride solution for about 8h for self-polymerization. Then, the fiber membrane was ultrasonically treated for 10min to remove excess PDA particles adhering to the nanofibers, rinsed three times with deionized water, and dried at 80℃ for 6h to obtain a PDA-PAN3 nanofiber membrane.

[0071] 2) Preparation of Co / Zn-MOF@PDA-PAN nanofiber membrane: The PDA-PAN3 nanofiber membrane was placed in a mixed solution of Co(AC)2·4H2O and Zn(NO3)2·6H2O with a concentration of 1.0 mol / L, and reacted at room temperature for 2 h. The fiber membrane was then immersed in a 0.16 mol / L 2-MIM solution and reacted for 12 h. The membrane was then rinsed with deionized water and dried at 50°C to obtain a Co / Zn-MOF@PDA-PAN0.16 nanofiber membrane.

[0072] Example 6

[0073] The preparation method and application of bimetallic MOF modified nanofiber membrane with antibacterial properties include the following steps:

[0074] 1) Preparation of PDA-PAN nanofiber membrane: Weigh 1.76g PAN and add it to 10g DMF, stir for 10h to obtain a 15wt% solution. Then add 0.2g polyethylene glycol and stir magnetically for 25min to obtain PAN spinning solution. The spinning solution is loaded into a syringe and an electrospinning machine is used to form a PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1.5mL / h, receiving distance 20cm, spinning time 4h, humidity <30%. The PAN fiber membrane was immersed in a 1mg / mL dopamine hydrochloride solution for about 12h for self-polymerization. Then, the fiber membrane was ultrasonically treated for 10min to remove excess PDA particles adhering to the nanofibers, rinsed three times with deionized water, and dried at 80℃ for 6h to obtain a PDA-PAN1 nanofiber membrane.

[0075] 2) Preparation of Co / Zn-MOF@PDA-PAN nanofiber membrane: The PDA-PAN1 nanofiber membrane was placed in a mixed solution of Co(AC)2·4H2O and Zn(NO3)2·6H2O with a concentration of 1.0 mol / L, and reacted at room temperature for 2 h. The fiber membrane was then immersed in a 0.24 mol / L 2-MIM solution and reacted for 12 h. The fiber membrane was then rinsed with deionized water and dried at 50°C to obtain a Co / Zn-MOF@PDA-PAN0.24 nanofiber membrane.

[0076] Example 7

[0077] The preparation method and application of bimetallic MOF modified nanofiber membrane with antibacterial properties include the following steps:

[0078] 1) Preparation of PDA-PAN nanofiber membrane: Weigh 1.76g PAN and add it to 10g DMF, stir for 10h to obtain a 15wt% solution. Then add 0.4g polyethylene glycol and stir magnetically for 25min to obtain PAN spinning solution. The spinning solution is loaded into a syringe and an electrospinning machine is used to form a PAN nanofiber membrane. Spinning parameters: spinning voltage 21kV, spinning speed 1.5mL / h, receiving distance 20cm, spinning time 4h, humidity <30%. The PAN fiber membrane was immersed in a 1mg / mL dopamine hydrochloride solution for about 12h for self-polymerization. Then, the fiber membrane was ultrasonically treated for 10min to remove excess PDA particles adhering to the nanofibers, rinsed three times with deionized water, and dried at 80℃ for 6h to obtain a PDA-PAN1 nanofiber membrane.

[0079] 2) Preparation of Co / Zn-MOF@PDA-PAN nanofiber membrane: The PDA-PAN1 nanofiber membrane was placed in a mixed solution of Co(AC)2·4H2O and Zn(NO3)2·6H2O with a concentration of 1.0 mol / L, and reacted at room temperature for 2 h. The fiber membrane was then immersed in a 0.16 mol / L 2-MIM solution and reacted for 12 h. The fiber membrane was then rinsed with deionized water and dried at 50°C to obtain a Co / Zn-MOF@PDA-PAN0.16 nanofiber membrane.

[0080] Example 8

[0081] The 2-methylimidazole in step 2) of Example 3 was replaced by 2-methylbenzimidazole, and the other conditions were the same as those of Example 3.

[0082] Example 9

[0083] The 2-methylimidazole in step 2) of Example 3 was replaced by 2-ethylimidazole, and the other conditions were the same as those of Example 3.

[0084] Example 10

[0085] The polyethylene glycol in step 1) of Example 6 was replaced by zinc chloride, and the other conditions were the same as those of Example 6.

[0086] Embodiment 11

[0087] The polyethylene glycol in step 1) of Example 6 was replaced by calcium carbonate, and the other conditions were the same as those of Example 6.

[0088] Example 12

[0089] The concentration of the PAN spinning solution in step 1) of Example 7 was changed to a 10 wt % solution, and the other conditions were the same as those of Example 7.

[0090] Example 13

[0091] The concentration of the PAN spinning solution in step 1) of Example 7 was changed to a 12 wt % solution, and the other conditions were the same as those of Example 7.

[0092] Embodiment 14

[0093] The concentration of the mixed solution of Co(AC)2·4H2O and Zn(NO3)2·6H2O in step 2) of Example 7 was changed to 1.2 mol / L, and the reaction was carried out at room temperature for 2 h. Other conditions were the same as those of Example 7.

[0094] Embodiment 15

[0095] The concentration of the mixed solution of Co(AC)2·4H2O and Zn(NO3)2·6H2O in step 2) of Example 7 was changed to 2.0 mol / L, and the reaction was carried out at room temperature for 1 h. Other conditions were the same as those of Example 7.

Claims

1. Preparation method and application of bimetallic MOF modified nanofiber membrane with antibacterial properties, characterized in that The steps include: 1) Preparation of PDA-PAN nanofiber membrane: polyacrylonitrile (PAN) and porogen are added to an organic solvent, stirred and mixed evenly at room temperature, and electrospun to obtain primary fibers. The primary fibers are soaked to remove the porogen, and then dried to obtain a PAN nanofiber membrane. A certain amount of dopamine hydrochloride is dissolved in a Tris-HCl buffer solution, and the PAN nanofiber membrane is soaked in the above solution for self-polymerization. Then, the polydopamine (PDA) modified PAN nanofiber membrane is ultrasonically treated to remove excess PDA particles adhering to the nanofibers, and the PDA-PAN nanofiber membrane is obtained after air drying. The porogen increases the surface area of ​​the fiber membrane, thereby increasing the active sites for MOF growth. 2) Preparation of bimetallic MOF modified nanofiber membrane: The PDA-PAN nanofiber membrane was placed in a mixed solution of bimetallic salts (cobalt acetate and zinc nitrate) with a concentration of 0.5-5 mol / L, and reacted at room temperature for 0.5-2 h. The fiber membrane was then immersed in a certain concentration of organic ligand (2-methylimidazole, 2-MIM) solution and reacted for 6-24 h. The membrane was then rinsed with deionized water and dried at 50°C to obtain a bimetallic MOF modified nanofiber membrane (Co / Zn-MOF@PDA-PAN nanofiber membrane). The organic ligand 2-MIM has good solubility and stability, can form coordination bonds with metal ions, help the formation and crystal growth of zeolitic imidazolate framework (ZIF), improve the preparation efficiency and quality of ZIF, and can control the lattice structure and pore size of ZIF, so that ZIF has better application performance.

2. The method for preparing a bimetallic MOF-modified nanofiber membrane with antibacterial properties as claimed in claim 1, characterized in that: The porogen in step 1) is ethanol, isopropanol, acetone, polyvinyl pyrrolidone, polyethylene glycol, zinc chloride or calcium carbonate.

3. The method for preparing a bimetallic MOF-modified nanofiber membrane with antibacterial properties as claimed in claim 1, characterized in that: The organic solvent in step 1) is one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide or a mixed solvent thereof.

4. The method for preparing a bimetallic MOF-modified nanofiber membrane with antibacterial properties as claimed in claim 1, characterized in that: The conditions for electrospinning in step 1) are: voltage of 18-23 kV, receiving distance of 10-30 cm, spinning solution flow rate of 0.5-2 mL / h, spinning temperature of 20-30° C., humidity of 20-40%; and the needle used is a 19-23 gauge needle.

5. The method for preparing a bimetallic MOF-modified nanofiber membrane with antibacterial properties as claimed in claim 1, characterized in that: The concentration of the dopamine hydrochloride solution in step 1) is 1-10 mg / mL.

6. The method for preparing a bimetallic MOF-modified nanofiber membrane with antibacterial properties as claimed in claim 1, characterized in that: The concentration of the organic ligand in step 2) is 0.08 mol / L to 0.96 mol / L.

7. The method for preparing a bimetallic MOF-modified nanofiber membrane with antibacterial properties as claimed in claim 1, characterized in that: The organic ligand in step 2) is 2-ethylimidazole, 2-propylimidazole, 2-isopropylimidazole, 2-methylbenzimidazole, 2-methyl-4-ethylimidazole, 2-methyl-4-isopropylimidazole, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, etc.

8. The method for preparing a bimetallic MOF-modified nanofiber membrane with antibacterial properties as claimed in claim 1, characterized in that: The molar ratio of the bimetallic salt to the organic ligand in step 2) is 3:1 to 1:3; the molar ratio of the bimetallic salt is 5:1 to 1:

5.

9. The method for preparing a bimetallic MOF-modified nanofiber membrane with antibacterial properties as claimed in claim 1, characterized in that: The bimetallic salt in step 2) is copper nitrate, zirconium nitrate, nickel nitrate, ferric chloride, etc.

Citation Information

Patent Citations

  • Preparation method of amino acid graft nanofiber membrane for bilirubin adsorption

    CN108103662A

  • Preparation method and application of polydopamine modified ZIF-8 functionalized nanofiber membrane

    CN109577005A

  • Method for reinforcing ultraviolet resistance of fibers by loading transition metal ions on fiber surface

    CN110685157A

  • Application of bimetallic type MOFs-polydopamine-non-woven fabric in heavy metal ion adsorption

    CN115282938A

  • Process for the preparation of mofs-porous polymeric membrane composites

    US20150367294A1

Cited By

  • Composite nanofiber membrane as well as preparation method and application thereof

    CN120481406A